Pengaruh Testimoni dan Brand Ambassador Korea Terhadap Minat Beli Skincare Scarlett di TikTok Shop Pada Masyarakat Kabupaten Tasikmalaya - Dea Asri; Sri Sudiarti (CV. Muris Global Education, 2026)
This study aims to evaluate the extent to which testimonials and Korean brand ambassadors influence consumer purchase intention for Scarlett products on TikTok Shop. The research is based on concepts related to testimonials, brand ambassadors, and consumer purchase intention. Primary data were obtained using a purposive sampling technique. Data were collected through a Google Form distributed to TikTok users in Tasikmalaya Regency, with 106 respondents. Data analysis was conducted using an outer model approach, an inner model approach, and hypothesis testing. The uniqueness of this study lies in the use of SmartPLS-based SEM methods to analyze the relationships between variables. The results indicate that testimonials and Korean brand ambassadors have a positive and significant influence on consumer purchase intention.